Ixodes ricinus immatures on birds in a focus of Lyme borreliosis - Humair, P F; Turrian, N; Aeschlimann, A; Gern, L (Folia parasitologica, 1993)
The infestation of birds by immature Ixodes ricinus was studied during 6 months in a Swiss woodland, where Lyme borreliosis is endemic. Thirteen passerine species were found to be parasitized by I. ricinus subadults and specially Turdus merula, T. philomelos and Erithacus rubecula. Overall, 300 larvae and 162 nymphs were collected on 95 avian hosts. Prevalence of infestation of nymphs on birds was higher in spring; larvae peaked in summer. The infection of birds by Borrelia burgdorferi was also studied using blood cultivation and examination of ticks. Motionless spirochetes were isolated from two E. rubecula. Infected ticks were removed from five species of passerines, and mainly three species of Turdidae (T. merula, T. philomelos and E. rubecula). Infection rate of larvae and nymphs by spirochetes averaged 16.3% and 21.7%, respectively. These percentages, compared to the infection rate of questing ticks collected through dragging, suggest that some Turdidae may play a role as amplifying hosts for spirochetes in the focus.
Keywords: Ticks; Disease Reservoirs; ptáci; Birds; Borrelia; Arachnid Vectors; nemoci ptáků; lymeská nemoc; Lyme Disease; zdroje nemoci; zvířata; Švýcarsko; arachnida jako vektory; roční období; klíšťata; Switzerland; Seasons; infestace klíšťaty; Animals; Tick Infestations; Bird Diseases